2012
DOI: 10.1371/journal.pcbi.1002429
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Binding Site: The Role of the β2 – β3 Loop and Extra-Domain Structures in PDZ Domains

Abstract: A general paradigm to understand protein function is to look at properties of isolated well conserved domains, such as SH3 or PDZ domains. While common features of domain families are well understood, the role of subtle differences among members of these families is less clear. Here, molecular dynamics simulations indicate that the binding mechanism in PSD95-PDZ3 is critically regulated via interactions outside the canonical binding site, involving both the poorly conserved loop and an extra-domain helix. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 49 publications
5
52
0
Order By: Relevance
“…25,26 In MAGI PDZ1 for example, an extended C-terminal loop makes direct interactions with Arg -4 , Arg -5 and Thr -6 of the peptide ligand and mutation in this C-terminal loop decreases the binding affinity drastically. 27 Thus, from previous work 11,12,14,24,27 together with the present data we conclude that some PDZ domains contain certain structural elements at their C-terminus, which have a direct effect on binding affinity. …”
Section: Discussionsupporting
confidence: 84%
“…25,26 In MAGI PDZ1 for example, an extended C-terminal loop makes direct interactions with Arg -4 , Arg -5 and Thr -6 of the peptide ligand and mutation in this C-terminal loop decreases the binding affinity drastically. 27 Thus, from previous work 11,12,14,24,27 together with the present data we conclude that some PDZ domains contain certain structural elements at their C-terminus, which have a direct effect on binding affinity. …”
Section: Discussionsupporting
confidence: 84%
“…6C). The role of the interaction between β2-β3 loop and α3 helix has been already shown in an earlier study (51). Interestingly, there exists a significant population (6%) for the intrahelical i − i + 4 salt bridge formation between the side chains of E395-R399 in the unbound state (Fig.…”
Section: Population Shift Of Hydrogen-bonded Network Leads To Allostericsupporting
confidence: 68%
“…However, the strongest effects were observed for residues 329–334, which are located in the β2–β3 loop. Interactions between residues in this loop of PSD-95-PDZ3 and the side chain of Lys-4 in KKETAV have been proposed previously [33]. Furthermore, binding studies have revealed a determinant role of Lys-4 in the binding affinity of KKETAV, although this interaction was not observed in the crystal structure of the complex due to lack of resolution of the Lys-4 side chain [19].…”
Section: Resultsmentioning
confidence: 91%